Ten years of the new Russia - Francesc Serra Massansalvador (Revista CIDOB d'Afers Internacionals, 2002)
This article analyzes developments in Russia since the breaking-up of the Soviet Union in 1991. Given this objective, the author places particular emphasis on the debate on social and identity issues raised by the political and ideological transition from a USSRconsidered a superpower to a country that aspire to achieving political and economic stability and, ultimately, to retaining a limited area of influence as a regional power. In this, Russia has received strong, unconditional international support, which has allowed it to overcome various obstacles, but the difficult transition that the country has been through has made it impossible to avoid a severe collective trauma in terms of ideology and identity. The process has clearly been also accompanied by a significant disregard for the individual and collective rights of the Russian people, a price that, in the long term, may be too high a one to pay for a population that aspires to stability and for a countrythat aspires to respect and to equality with the rest of the world.